Inhibition of human platelet aggregation by Choisyaternatine isolated from Choisya ternata (Rutaceae) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2021)
A newly reported alkaloid was isolated from the hexane extract of Choisya ternata Kunth. (Rutaceae) leaves, identified as 6,8-Dimethoxy-7-(3-methylbut-2-enyloxy)quinolin-2-ol (choisyaternatine) (A), together with the known compounds skimmianine (B), lup-20(29)-en-3?-ol (lupeol) (C) and tecleamaniensine A (D). Compounds C and D are reported for the first time in this species. The structures of isolated compounds were elucidated by extensive spectroscopic analyses and comparison with previously reported spectroscopic data. The structure of choisyaternatine was further confirmed based on X-ray data analysis. Anti-platelet activity of hexane extract, choisyaternatine and skimmianine was also evaluated. The extract was able to significantly inhibit collagen-induced platelet aggregation at all concentrations tested (25, 50 and 100 µg/ml). The new compound, choisyaternatine, has shown a significant inhibition of collagen-induced platelet aggregation demonstrated in a concentration dependent manner from 250 µM. The concentrations which inhibit 50% of platelet aggregation (IC50) were found to be 564 µM for skimmianine and 698 µM for choisyaternatine. This is also the first report for the antiplatelet activity for this plant and these alkaloids using human platelets.
Keywords: Choisya ternata; platelet aggregation; choisyaternatine; skimmianine